Compudose® vs Ralgro®/Synovex-S® or Synovex-S®/Synovex-S® Reimplant programs for finishing yearling steers - Laudert, S.B.; Lee, R.W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three field trials were conducted with finishing yearling steers to compare the performance of cattle receiving Compudose® or Ralgro®/Synovex-S® and Synovex-S®/Synovex-S® reimplant combinations. No differences were found between Compudose and the reimplant programs in cattle daily gain, feed efficiency, or cost of gain. Compudose retention was 97.5% in the 1317 head implanted. Synovex-S implant site abscess rate ranged from 5.7 to 15.4%.
Keywords: Beef; Compudose® vs Ralgro®; Reimplant; Steers